INCREASING INVENTORY MANAGEMENT EFFICIENCY AT PT. XYZ'S MACHINE WORKSHOP THROUGH INTEGRATED APPLICATION DESIGN STRATEGY - Nurwahidah, Andi; Sawal, Ahmad; Baharuddin, Andi Velahyati; Natsir, A Dian Sry Rezky; Lifana, Azizah Salsabila (Journal of Industrial Engineering Management, 2024)
PT XYZ has a machine workshop unit that serves as a support system for the smooth operation of the factory. The machine workshop contains a tools area that houses consumable materials and equipment. The process of recording materials and equipment in the machine workshop still relies on Microsoft Excel, which takes a long time for the person in charge (PIC) to input data, especially when accessing the computer. Furthermore, supervisors and managers cannot directly monitor the materials and equipment. Therefore, a mobile application is needed to address these issues. The objective of this research is to design an inventory application for materials and equipment. The system design involves using data flow diagrams and utilizing Google Access as the database, along with AppSheet for application development. Based on operational results, it was found that this application can simplify data input for the PIC and enable monitoring by supervisors and managers.